The Opportunities and Challenges for Hadith Studies among Orientalists (International Journal of Scientific Research and Management (IJSRM), 2025)
This study discusses the opportunities and challenges of hadith studies among Orientalists. Orientalism as the study of the Eastern world, especially Islam, has a complex history and development. Over time, orientalism turned into a political and social tool used to attack and denigrate Islam and to protect the Christian community from the threat of Islam. The change in focus from general Islamic studies to hadith studies shows the evolution of orientalism in exploring specific aspects of Islam. The method in this study is a qualitative research method, namely by formulating research ideas, collecting data, analyzing data, and concluding research results. The type of research used is library research, which involves searching and collecting information from various sources in the library. The results of this study show that although the general view among Muslims tends to be suspicious of orientalism as a tool of Western ideology to undermine Islam, a critical and objective approach to orientalism can help enrich Islamic discourse and open the door to constructive criticism from different points of view. Confronting Orientalists in hadith studies is not an easy task for Muslim scholars as they are faced with the challenge of maintaining the integrity and autonomy of their hadith studies under the glare of Orientalist criticism and evaluation. However, hadith studies among Orientalists also offer great opportunities to broaden academic understanding and promote interreligious dialogue, which can be undertaken with an objective and professional approach and with due regard for methodological differences and diverse views.